1870 La. Acts 159 - 60, An Act to Regulate the Conduct and to Maintain the Freedom of Party Election . . ., § 73 - (:unkn) unknown (General Publisher, 1870)
Prohibited the carrying of a concealed or open gun, pistol, Bowie knife or other dangerous weapon on an election day during the hours the polls are open or during registration. Punishable by fine of minimum $100 and imprisonment of minimum 1 month.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES